2009
DOI: 10.1097/01.ncq.0000356909.79829.4e
|View full text |Cite
|
Sign up to set email alerts
|

Patients' Perception of Monitoring During Cardiac Rehabilitation

Abstract: Graduates of a cardiac rehabilitation program reported they did not use self-monitoring skills at home. This unexpected outcome led to an investigation of the reasons for this lack of use. Results of the study informed program revision including the teaching tool and teaching strategies designed to enhance program effectiveness and improve patient outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 13 publications
2
7
0
2
Order By: Relevance
“…However, it was reported that patients with chronic heart failure have poor ability to recognize exercise early warning, and only by judging the critical value of exercise indicators and self-feelings to adopt appropriate exercise intensity during home-based cardiac rehabilitation exercise. 46 Accordingly, it is necessary for patients with chronic heart failure to receive the relevant technical supports and education from cardiac rehabilitation professionals to promote the ability to identify exercise risk warnings and adherence behavior. In addition, there are great differences in exercise monitoring among patients with chronic heart failure for the heterogeneity of education level.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was reported that patients with chronic heart failure have poor ability to recognize exercise early warning, and only by judging the critical value of exercise indicators and self-feelings to adopt appropriate exercise intensity during home-based cardiac rehabilitation exercise. 46 Accordingly, it is necessary for patients with chronic heart failure to receive the relevant technical supports and education from cardiac rehabilitation professionals to promote the ability to identify exercise risk warnings and adherence behavior. In addition, there are great differences in exercise monitoring among patients with chronic heart failure for the heterogeneity of education level.…”
Section: Discussionmentioning
confidence: 99%
“…Minimal change and poor adherence to diet regimens 2 mo post-CR and significant worsening of dietary scores after 1-yr follow-up have been described in patients in CR. 30,54,55 One CR study assessing nine micronutrients important in cardiovascular health (vitamin C, vitamin E, vitamin A, vitamin B 12 , vitamin B 6 , folate, potassium, sodium, and magnesium) at baseline, during, and 6 mo post-CR found the levels of micronutrients insufficient in meeting the dietary reference intake levels in a population with good adherence to the program. 56 Another study assessed 5-yr follow-up of patients in CR after intervention with an expanded 1-yr CR program including increased education on diet and counseling and three 3-hr weekly cooking sessions led by a dietitian.…”
Section: Nutrition Interventions In Cardiac Rehabilitationmentioning
confidence: 99%
“…Studies on the short- and long-term dietary outcomes in patients in CR are limited. Minimal change and poor adherence to diet regimens 2 mo post-CR and significant worsening of dietary scores after 1-yr follow-up have been described in patients in CR 30,54,55. One CR study assessing nine micronutrients important in cardiovascular health (vitamin C, vitamin E, vitamin A, vitamin B 12 , vitamin B 6 , folate, potassium, sodium, and magnesium) at baseline, during, and 6 mo post-CR found the levels of micronutrients insufficient in meeting the dietary reference intake levels in a population with good adherence to the program 56.…”
Section: Review Of Relevant Literaturementioning
confidence: 99%
“…However, the treatments have been shown to be unsuccessful in helping cardiac patients reach similar intensity once the program was completed at home. One of the reasons reported for not reaching the recommended intensity after the program was the absence of tools (eg, heart-rate [HR] monitor) to help them to identify the correct intensity as they had in the supervised program 9. In the past, studies attempted to determine whether people could identify moderate-to-vigorous intensity by comparing self-perceived exertion scores with their HR1015 and reported low to moderate associations depending on the methodology used.…”
Section: Introductionmentioning
confidence: 99%